The Emergence and the Objective of Islamic Medicine for the Preservation of Health - Deuraseh, Nurdeen (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Emergence and the Objective of Islamic Medicine for the Preservation of Health